MEDAN CUSTOMER PERCEPTION OF INSTANT NOODLE INFLUENCE TOWARDS CUSTOMERS PURCHASE INTENTION - Daniel Cassa Augustinus; Vivi Vivi (Journal of Accounting and Management Innovation, 2020)
The purpose of this study is to analysis whether there is any influence of Perceived value towards Customers purchase intention in Wakaka Medan. This research might help other researcher to get more information about this topic. Perceived value is considered as a customer that comparing the benefits to be received with the sacrifice that they made to obtain a product / service which can increase customers purchase intention. For the research design the researcher using quantitative method as the research design The writers using IBM SPSS Statistic 25. The data use in this research are primary and secondary data. For the data analysis method, the writer used descriptive statistic, validity & reliability, normality test, correlation coefficient test, determination test, linear regression test and t test. The result of the normality test shows that the questioner is normally distributed. While the coefficient of correlation test and coefficient of determination test shows that Perceived Value have a weak relationship towards Purchase Intention. After done with the research and analysis, can be conclude that Perceived Value have a weak relationship towards Purchase Intention in Wakaka Medan.Keywords: Perceived Value, Purchase Intention, Influence between perceived value and purchase intention.